How might contact with nature promote human health? Promising mechanisms and a possible central pathway - Kuo, Ming (Frontiers in Psychology, 2015)
How might contact with nature promote human health? Myriad studies have linked the two; at this time the task of identifying the mechanisms underlying this link is paramount. This article offers: (1) a compilation of plausible pathways between nature and health; (2) criteria for identifying a possible central pathway; and (3) one promising candidate for a central pathway. The 21 pathways identified here include environmental factors, physiological and psychological states, and behaviors or conditions, each of which has been empirically tied to nature and has implications for specific physical and mental health outcomes. While each is likely to contribute to nature’s impacts on health to some degree and under some circumstances, this paper explores the possibility of a central pathway by proposing criteria for identifying such a pathway and illustrating their use. A particular pathway is more likely to be central if it can account for the size of nature’s impacts on health, account for nature’s specific health outcomes, and subsume other pathways. By these criteria, enhanced immune functioning emerges as one promising candidate for a central pathway between nature and health. There may be others.